PARTICIPATORY LAND USE CONFLICT RESOLUTION: EFFORTS TOWARDS COMMUNITY COLLABORATIVE MANAGEMENT - Golar Golar; Sudirman Dg Massiri; Rustam Abd Rauf; Hasriani Muis; Syahril Paingi (Universitas Tadulako, 2021)
This research aims to determine the causes of land-use conflicts and formulate a participatory conflict resolution model of the Forest Management Unit (KPH) of Kulawi. Through interviews with respondents using the purposive sampling method. The study included the community around the forest area, local government, KPH, Department of Agriculture, BPDAS-HL, and local government. Data analysis was stakeholder's and land use conflict by using problem trees analysis. The study results show that the battle occurred not only because of the community's factor of accessing the area illegally but also because the KPH has not performed its function correctly. Some factors cause enforcement's failure, such as lack of understanding of the area and community empowerment. Some alternative solutions desired by the community: (1) The government through related agencies should supervise forest areas, (2) Clear boundaries between community-owned land, villages, and forest areas, (3) Community empowerment by utilizing potential forest product resources and (4) Granting management rights to community's forest claimed by the community. There are two models of conflict resolution to be offered. First, the KPH needs the collaboration of parties to resolve land-use conflicts. Second, community involvement as the main subject is significant in every stage of conflict resolution. The KPH supports improving community capacity related to competence in conflict resolution is indispensable.